1992
DOI: 10.1136/jmg.29.11.827
|View full text |Cite
|
Sign up to set email alerts
|

Orofaciodigital syndrome type I in a girl with unilateral tibial pseudarthrosis.

Abstract: The orofaciodigital syndromes are a group of possibly seven different malformation syndromes including oral, facial, and digital malformations. Type I has X linked dominant inheritance whereas the other types show autosomal recessive inheritance. An exact diagnosis is therefore important for genetic counselling. We here report a girl with orofaciodigital syndrome type I. She had cystic kidney disease at the age of 8 months which has not previously been reported in an infant with orofaciodigital syndrome. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Malformations of the hands include clinodactyly, syndactyly, and brachydactyly. Orstavik et al (1992) reported a case with unilateral duplication of the big toe associated with ipsilateral bowing of the tibia, thought to represent a pseudarthrosis.…”
Section: Discussionmentioning
confidence: 97%
“…Malformations of the hands include clinodactyly, syndactyly, and brachydactyly. Orstavik et al (1992) reported a case with unilateral duplication of the big toe associated with ipsilateral bowing of the tibia, thought to represent a pseudarthrosis.…”
Section: Discussionmentioning
confidence: 97%